Lewis Acids and Heteropoly Acids in the Synthesis of Organic Peroxides - Yaremenko, Ivan A.; Radulov, Peter S.; Belyakova, Yulia Yu.; Fomenkov, Dmitriy I.; Tsogoeva, Svetlana; Terent'Ev, Alexander O. (Pharmaceuticals, 2022)
Organic peroxides are an important class of compounds for organic synthesis, pharmacological chemistry, materials science, and the polymer industry. Here, for the first time, we summarize the main achievements in the synthesis of organic peroxides by the action of Lewis acids and heteropoly acids. This review consists of three parts: (1) metal-based Lewis acids in the synthesis of organic peroxides; (2) the synthesis of organic peroxides promoted by non-metal-based Lewis acids; and (3) the application of heteropoly acids in the synthesis of organic peroxides. The information covered in this review will be useful for specialists in the field of organic synthesis, reactions and processes of oxygen-containing compounds, catalysis, pharmaceuticals, and materials engineering.
CRIS-Team WoS Importer:2022-05-06